Institutional Dualism in Mukim Forest Governance: A Green Politics Perspective in Peudada, Aceh - Amri Wahid Hidayat; Akmal Saputra; Ikhwan Rahmatika Latif; Yeni Sri Lestari; Mufazzal (NeoRespublica : Jurnal Ilmu Pemerintahan, 2026)
This study examines the authority of Imum Mukim in the sustainable governance of customary forests in Peudada Subdistrict, Bireuen Regency, Aceh, from a Green Politics perspective. Although Mukim institutions are formally recognized within Aceh’s legal framework, their practical authority in forest governance remains weak and marginal. This research aims to analyze the causes of this institutional paradox and to explain why Mukim functions merely as a normative actor rather than an effective governing authority. Using qualitative library-based research supported by document analysis of legal instruments, policy documents, and relevant academic literature, this study applies Green Politics and Political Ecology frameworks to interpret the gap between formal recognition and practical authority. The findings reveal a persistent institutional dualism in Mukim governance: while Mukim holds strong normative and cultural legitimacy, it lacks regulative and enforcement power due to regulatory fragmentation, state-centric forest governance, and power asymmetries with corporate and bureaucratic actors. As a result, Mukim operates as a “phantom institution” recognized symbolically but excluded substantively from decision-making processes. This study concludes that strengthening customary forest governance requires not only legal recognition but also institutional integration, regulatory coherence, and redistribution of authority toward indigenous governance structures. These findings contribute to Green Politics debates on ecological justice and local sustainability.